1992
DOI: 10.1037/0735-7044.106.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Blood ethanol concentration from early postnatal exposure: Effects on memory-based learning and hippocampal neuroanatomy in infant and adult rats.

Abstract: Early postnatal exposure to ethanol (EtOH) that results in daily high-peak blood ethanol concentration (BEC) retarded the acquisition of single-patterned alteration (PA), a kind of memory-based discrimination learning, and was related to reduced brain weight, hippocampal cell number, and CA1 area in infant rats. These behavioral and neuroanatomical effects survived into young adulthood. On the PA discrimination, in both pups and young adults, postnatal exposure to high-peak EtOH condition, in relation to low-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
59
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 43 publications
7
59
1
Order By: Relevance
“…This study is in agreement with previous studies finding that alcohol exposure during the neonatal period results in a reduction in the number of CA1 pyramidal cells West, 1990, 1991;Diaz-Granados et al, 1993;Greene et al, 1992;Miller, 1995;Tran and Kelly, 2003). However, it is the first study to show this effect in this exposure model (PD7-9), which is a relatively short time period during the brain growth spurt.…”
Section: Ca1 Cell Numbersupporting
confidence: 94%
“…This study is in agreement with previous studies finding that alcohol exposure during the neonatal period results in a reduction in the number of CA1 pyramidal cells West, 1990, 1991;Diaz-Granados et al, 1993;Greene et al, 1992;Miller, 1995;Tran and Kelly, 2003). However, it is the first study to show this effect in this exposure model (PD7-9), which is a relatively short time period during the brain growth spurt.…”
Section: Ca1 Cell Numbersupporting
confidence: 94%
“…Stone et al (1996) also reported deficits in radial arm maze performance in prenatal alcohol-exposed rats. The same rats were not impaired in passive avoidance, suggesting that spatial performance may be a more sensitive behavioral measure of alcohol teratogenicity in the hippocampus than response inhibition Greene et al, 1992).…”
Section: Radial Arm Mazementioning
confidence: 95%
“…Greene et al (1992) reported significant reductions in the CA 1 area and pyramidal cell counts on both PN21 (ϳ10% decrease) and PN60 (ϳ20% decrease) after neonatal binge alcohol exposure concentrated into four of 24 daily administrations. However, when the same total daily dose was distributed across all 24 administrations each day, there were no significant effects in the hippocampus (Greene et al, 1992).…”
Section: Cell Lossmentioning
confidence: 96%
See 1 more Smart Citation
“…Although the effects of short binges of alcohol exposure on other brain regions are largely unknown, bingelike alcohol exposure throughout the early postnatal period is known to produce reductions in pyramidal cell density in hippocampal field CAI (Bonthius & West, 1990Greene, Diaz-Granados, & Amsel, 1992) and transient reactive astrogliosis in the cerebral cortex (Goodlett, Leo, O'Callaghan, Mahoney, & West, 1993). These anatomical effects in limbic and cortical areas suggest that neonatal alcohol exposure may also affect brain structures thought to be functionally important for spatial (e.g., Olton, 1983) and temporal (e.g., Greene et al, 1992) discriminations, raising two additional questions: Are other behaviors that engage certain cognitive processes (e .g., spatial working memory) also affected by short binge exposures? Do such alcohol-related effects on cognitive performance show windows of vulnerability comparable to effects on motor performance?…”
Section: Introductionmentioning
confidence: 99%